A guideline for greenhouse gas emission reduction and carbon sequestration in forest sector based on Thailand voluntary emission reduction programme - Yannawut Uttaruk; Khoa, Phung Van; Teerawong Laosuwan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Currently climate change and global warming have significant impact on the environment toward biodiversity and human quality of life. Major cause derives from human activities that produce greenhouse gas emission especially the diffusion of carbon dioxide to the atmosphere. One way to address global warming is to increase the absorption potential of greenhouse gases, especially carbon dioxide. The best natural method is forest adsorption whereby trees absorb carbon dioxide and store it in the form of biomass through photosynthesis. Therefore, forests are a highly efficient source of carbon sinks. The main objective of this research was to implement a methodology for greenhouse gas reduction and carbon sequestration assessments in forest sector according to Thailand’s standards known as the Thailand Voluntary Emission Reduction Program (T-VER). According to climate change, reduction of greenhouse gas process will use methodology of T-VER-METH-FOR-01 Version 2 (Sustainable Forestation) and T-VER-TOOL-FOR/ AGR-01 Version 2 (Calculation for Carbon Sequestration). The Baseline Sequestration/Emission and Project Sequestration/ Emission as well as plant diversity assessment in project area as greenhouse gas activity will be used for the calculation. The results of this development of prototype project could be used for concluding content of greenhouse gas from 134.72 ha of the research area and it was shown that Baseline Sequestration was 19,618.95 tCO2 e. When calculating Project Sequestration for 10 years, carbon content could be increased by 27,617.95 tCO2 e calculated to be 800.61 tCO2e/yr. Therefore, total Project Sequestration was 8,006.13 tCO2 e.